Pengenalan dan Pelatihan Penggunaan Aplikasi Mendeley dalam Karya Tulis Ilmiah untuk Persiapan Penulisan Proposal Skripsi Mahasiswa Jurusan Pendidikan Bahasa dan Sastra Indonesia - Eka Retnaningtyas, Hanova Rani (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity aims to introduce and train sixth-semester students in the use of the reference manager application Mendeley for academic writing, particularly for proposals and undergraduate theses. Based on initial findings, many students face difficulties in managing references and compiling bibliographies according to academic standards. Through this training activity, participants were guided from installation, library management, to integration with Microsoft Word. Evaluation results indicated an improvement in students' understanding and ability to use Mendeley. This activity provides a tangible contribution to enhancing students’ digital literacy and academic skills in scientific writing, especially in preparing their final thesis.